Infrastructure conditions of Brazilian schools: A needy school for the needy? - Duarte, Marisa Ribeiro Teixeira; Gomes, Carlos André Teixeira; Gotelib, Luciana Gonçalves de Oliveira (Education Policy Analysis Archives, 2019)
We analyzed the infrastructure conditions of Brazilian schools, aiming to expose their inequalities and territorial distribution. The literature review pointed an influence on previous studies of school infrastructure of regulation by outcomes on the educational system coordination and the limits of current redistributive policies in promoting greater inter federative equity. We tested the hypothesis of a poor school for the poor using the clusters analysis (use of K-means after application of hierarchical method, to determine the number of clusters and centroids). The three clusters obtained (adequate, intermediate and precarious) allowed us to trace the profiles of school infrastructure inequalities by constructing reference variables that expressed the quality of the good or service. Among the results obtained, there was a greater number of students from families participating in the “Bolsa Família” Program in public schools located in urban areas in the group called “adequate”, according to Brazilian standards. There was also a higher concentration of these students in municipal schools in rural areas of the “precarious” group, despite the reduced number of enrollments by Brazilian standards. We concluded by relating the reasons for the invisibility of these schools to the agendas of national public education policies.